How to create a national sport strategy - Kolar, Edvard (Annales kinesiologiae (Koper), 2024)
Purpose: Due to its numerous positive effects on individuals and society as a whole, sport has become an important socio-economic subsystem of the national environment. To regulate, develop, and monitor the impact of sport at national, regional, and local levels, countries often develop and adopt various strategic documents, which can be found under the name of national program or strategy for sport development at the national level. Due to the importance of understanding the substantial comprehensiveness of national sports strategies (NSS) and the precision of the methodological-processual approach, the purpose of the present paper is to present a methodological and sub-stantive view of the process of creating NSS and to develop a comprehensive concept (model) that appropriately places the substantive part in the phases of the process. Method: The methodology of writing conceptual research papers was used. This approach provides a bridge or link between different concepts and scientific disciplines. The methodological approach was the “model paper” which aims to provide a theoretical framework that predicts relationships between concepts. A model paper identifies connections between constructs and introduces new constructs. Findings: The development of the substantive model for the preparation of the NSS revealed that the comprehensive sport system at the national level can be understood within the framework of five substructures (financial, organizational, developmental, material, and program) that contribute significantly to the development and implemen-tation of activities related to sport and physical activity. They are interconnected and interdependent and are surrounded by a so-called integrity framework that protects the sport system from the deviations of modern society. The methodological process model reveals that for the implementation of the process of NSS preparation, the most appropriate is the strategic management methodology, which enables accurate and efficient management of planning, organization, implementation, and control of the NSS. The combination of both perspectives (substantive and methodological) enables the deve-lopment of a comprehensive concept (model) of NSS preparation. Conclusions: The developed concept (model) of the NSS preparation comprehensively covers the issue of the NSS preparation management and is dialectical, open, flexible, and repeatable, enabling future users to manage the NSS preparation in a substantive-holistic and process-effective manner.
Keywords: metodologija; metodološki pogled; nacionalna strategija športa; načrtovanje; šport; telesna aktivnost; upravljanje; vsebinski pogled